EOMES‐positive CD4+ T cells are increased in PTPN22 (1858T) risk allele carriers. Issue 4 (28th February 2018) - Chemin, Karine; Ramsköld, Daniel; Diaz‐Gallo, Lina‐Marcela; Herrath, Jessica; Houtman, Miranda; Tandre, Karolina; Rönnblom, Lars; Catrina, Anca; Malmström, Vivianne
Abstract: The presence of the PTPN22 risk allele (1858T) is associated with several autoimmune diseases including rheumatoid arthritis (RA). Despite a number of studies exploring the function of PTPN22 in T cells, the exact impact of the PTPN22 risk allele on T‐cell function in humans is still unclear. In this study, using RNA sequencing, we show that, upon TCR‐activation, naïve human CD4 + T cells homozygous for the PTPN22 risk allele overexpress a set of genes including CFLAR and 4‐1BB, which are important for cytotoxic T‐cell differentiation. Moreover, the protein expression of the T‐box transcription factor Eomesodermin (EOMES) was increased in T cells from healthy donors homozygous for the PTPN22 risk allele and correlated with a decreased number of naïve CD4 + T cells. There was no difference in the frequency of other CD4 + T‐cell subsets (Th1, Th17, Tfh, Treg). Finally, an accumulation of EOMES + CD4 + T cells was observed in synovial fluid of RA patients with a more pronounced production of Perforin‐1 in PTPN22 risk allele carriers. Altogether, we propose a novel mechanism of action of PTPN22 risk allele through the generation of cytotoxic CD4 + T cells and identify EOMES + CD4 + T cells as a relevant T‐cell subset in RA pathogenesis. Abstract : In healthy donors homozygous for the PTPN22 (1858T) risk allele, naïve CD4 + T cells exhibit increased expression of CFLAR and 4‐1BB upon TCR‐activation and increased EOMES + CD4 + T‐cell frequency. RA patients carrying the PTPN22 risk allele show a higher frequency of cytotoxic EOMES + CD4 + T cells in their joints.